2017
DOI: 10.1371/journal.pone.0188901
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nalbuphine and sufentanil for colonoscopy: A randomized controlled trial

Abstract: ObjectivesNalbuphine is as effective as morphine as a perioperative analgesic but has not been compared directly with sufentanil in clinical trials. The aims of this study were to compare the efficacy and safety of nalbuphine with that of sufentanil in patients undergoing colonoscopy and to determine the optimal doses of nalbuphine in this indication.MethodsTwo hundred and forty consecutive eligible patients aged 18–65 years with an American Society of Anesthesiologists classification of I–II and scheduled for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 25 publications
(22 reference statements)
0
25
1
1
Order By: Relevance
“…Jeleazcov, C et al found that PCA with hydromorphone offered satisfactory postoperative analgesic with respiratory insufficiency in 5% of the patients [11]. Correspondingly, Deng, C et al had reported that the risks of respiratory depression in patients undergoing colonoscopy was 33% by using sufentanil as a perioperative analgesia [30]. As mentioned above, hydromorphone also had a quicker therapeutic and better anti-inflammatory effect comparing with sufentanil.…”
Section: Discussionmentioning
confidence: 99%
“…Jeleazcov, C et al found that PCA with hydromorphone offered satisfactory postoperative analgesic with respiratory insufficiency in 5% of the patients [11]. Correspondingly, Deng, C et al had reported that the risks of respiratory depression in patients undergoing colonoscopy was 33% by using sufentanil as a perioperative analgesia [30]. As mentioned above, hydromorphone also had a quicker therapeutic and better anti-inflammatory effect comparing with sufentanil.…”
Section: Discussionmentioning
confidence: 99%
“…In the pilot experiment, we found patients with 2 mg•kg -1 of nalbuphine in 100 ml of saline for PICA had increased dizziness, and after the dosage of nalbuphine was reduced to 1 mg•kg -1 , the analgesic effect was equal, while dizziness was significantly reduced. Therefore, we used 1 mg•kg -1 of nalbuphine in 100 ml of saline for PICA for postoperative analgesia in Group N. However, despite using a lower dosage of nalbuphine for PCIA (the converted morphine dosage of Group N: the dosage of Group S=1:2), the VAS scores were lower in Group N than in Group S at postoperative 6 h, 12 h, and 24 h. This result is different from the study of Deng (10) and Gong(9) and similar to the study of Chen(14). This may be explained by a sex difference.…”
Section: Discussionmentioning
confidence: 76%
“…Nalbuphine can agitate the κ-opioid receptor to achieve an analgesic effect and antagonize the μopioid receptor to reduce the incidence of adverse reactions. It can be considered as a reasonable alternative to sufentanil, the μ-opioid receptor agonist, for varied surgical procedures (9,10,14). A study on the difference of the effects on the GI tract between them is still absent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary aim of the study was to investigate the effects of doxapram on low SpO 2 . Low SpO 2 was considered significant when SpO 2 was < 90% [6]. A face mask covering the patient’s nose and mouth was applied when the SpO 2 < 90%.…”
Section: Methodsmentioning
confidence: 99%